Ratio Analysis of Financial Reports to Measure Organizational Performance At PMI City of Surakarta - Sri Partini; Muhammad Luthfi H; Farrell Witamajaya (Nur Science Institute, 2023)
Community organizations, non-profit organizations must be responsible for all operational activities of the organization. This includes financial accountability to the public. Even though the service is the service performed social and humanitarian, but the performance of the organization must be goo. Especially financial performance for continuing service to the community. To find out the financial reports and financial performance at PMI Surakarta. This research is a quantitative approach, study with data collection, observation data with in-depth interviews and documentation and field studies at PMI Surakarta City. The financial report data used in this study are the 2019-2022 PMI Surakarta City financial reports. PMI Surakarta City is a non-profit organization that must remain strong to serve the community. one way to maintain the sustainability of the organization by measuring performance. Financial performance is one of them. To measure the financial performance of the authors using ratio analysis of financial statements. The analysis of liquidity ratio , solvability ratio, profitability ratio and activity ratio of financial reports PMI Surakarta in 2019 until 2021 viewed form the liquidity ratio from 2019 to 2021 PMI Surakarta was said to be liquid, because the company was able to cover the current debt and was able to increase its liquidity. Judging the organizations Solvency ratio is not stable. At 2019 to 2020 it decreased and then at 2020 to 2021 it increased. But in 2019 and 2021 the solvency ratio is the same. At 2019 to 2021 PMI Surakarta equity can cover its debt. Meanwhile, the profitability ratio seen from 2019 to 2021 always decreases. This was due to the impact of the covid pandemic and the task of the PMI sector was social humanity which at that time was indeed very important to distribute PMI funds to the community. so there are indeed a lot of costs incurred for the community. While seen from the activity ratio, from the total asset turn over ratio is a good performance. PMI Surakarta activity from 2019 to 2021 has increased the receipt of income is greater than assets. Even though PMI Surakarta is a non-profit organization, it is very important in measuring the financial performance of financial reports. This is to avoid unwanted events due to unfavorable financial conditions. By financial statements, it is expected to improve financial performance. Other sections of related units can also use this analysis report as a performance evaluation per section. If the performance is good, it will be able to provide good service too. In accordance with PMI's vision, to be tough and loved by the community.